Evidensdagsordenens metamorfoser i dansk socialpolitik - Møller, Anne Mette (Politik, 2017)
For almost two decades, the idea of evidence-based practice has influenced debates about the development of social services. Applying theoretical concepts from Scandinavian institutionalism, the article views evidence-based practice as a loosely coupled stream of ideas, which are continuously theorized and translated by heterogeneous organizational actors. Based on qualitative interviews with 10 political elite actors, who have all participated in the policy debate and had the opportunity to influence developments during the past 10 years, the analysis traces how these actors’ theorizations of evidence-based practice have developed over time, how they explain developments, and what characterizes their current theorizations. Two currently predominating theorizations are identified: One emphasizes the crucial challenge of advancing practitioners’ skills and building reflective organizations, while the other focuses on the production of evidence in relation to data-driven management. Both theorizations involve a shift in focus from global to local evidence production, while the ideal of the autonomous ‘evidence-based practitioner’, which characterized the original “Evidence-Based Medicine”-movement, is largely absent.